Amantadine ER (Gocovri®) Significantly Increases ON Time Without Any Dyskinesia: Pooled Analyses From Pivotal Trials in Parkinson's Disease - Hauser, Robert A.; Walsh, Ryan R.; Pahwa, Rajesh; Chernick, Dustin; Formella, Andrea E. (Frontiers in Neurology, 2021)
Background: Clinical trials for antiparkinsonian drugs aimed at managing motor complications typically use patient diaries to divide levodopa-induced dyskinesias (LID) into “troublesome” and “non-troublesome” categories. Yet, given the choice, most patients would prefer to live without experiencing any dyskinesia. However, the concept of evaluating time spent ON without any dyskinesia as an outcome has never been tested. We conducted analyses of pooled Gocovri pivotal trial data in order to evaluate the extent to which Gocovri increased the time PD patients spent ON without dyskinesia (troublesome or non-troublesome), beyond its already identified improvement in reducing troublesome dyskinesia. Methods: Patients enrolled in phase 3 trials (EASE LID [NCT02136914] or EASE LID 3 [NCT02274766]) recorded time spent in the following PD diary states at baseline and Week 12 (endpoint): asleep, OFF, ON with troublesome dyskinesia, ON with non-troublesome dyskinesia, and ON without dyskinesia. Mixed model repeated measures analyses with estimated Cohen D effect sizes were performed on the modified intent to treat population to evaluate changes in time spent in these states. Results: Patients randomized to receive Gocovri showed an increase in ON time without dyskinesia and corresponding decreases in ON time with dyskinesia and OFF time vs. placebo. Treatment effects were statistically significant for Gocovri vs. placebo starting at Week 2 and were sustained until Week 12. On MMRM analysis at Week 12, patients in the Gocovri group showed an adjusted mean ± SE increase over placebo of 2.9 ± 0.6 h in ON time without dyskinesia (Cohen D effect size 0.79) and an adjusted mean ± SE decrease of −1.9 ± 0.6 h in ON time with dyskinesia (troublesome + non-troublesome) (Cohen D effect size 0.49), that included a −1.5 ± 0.4 h placebo-adjusted reduction in ON time with troublesome dyskinesia and a −0.6 ± 0.4 h reduction in ON time with non-troublesome dyskinesia. OFF time was reduced by −1.0 ± 0.3 h compared to placebo. Conclusions: Gocovri treatment more than doubled the daily time patients spent ON without dyskinesia. These results suggest that the Gocovri treatment effect was driven by a reduction in overall motor complications including ON time with both troublesome and non-troublesome dyskinesia as well as time spent OFF.